Dietary patterns in stroke patients in Northwest India. (November 2013) - Mangat, Arshi; Grewal, Dilpreet; Kaur, Paramdeep; Jyotsna, Rashmi; Singh, Ruma; Pandian, Jeyaraj Durai
Abstract : Objectives: Little is known about the dietary patterns among stroke patients in India. We explored the dietary patterns in stroke patients and attempted to correlate the dietary patterns with stroke characteristics. Methods: This hospital-based study was carried out in a tertiary referral centre in Northwest India from March 2008 to September 2009. All first ever stroke (ischaemic and hemorrhagic) patients were interviewed by the dietician using an oral diet questionnaire. The demographic information and risk factors were noted and outcome was assessed after 30 days using modified Rankin scale (≤2 = good outcome). Results: A total of 210 stroke patients were enrolled. The mean age was 60 ± 14 years and 126 (60%) patients were men. Hypertension (167 (79.5%)) was the major risk factor. All patients consumed cereals and beverages. Consumption of other food items in the diet were as follows: milk and milk products (203 (96.7%)), saturated fats (butter, butter oil, cream) (133 (63.3%)), bakery items (139 (66.2%)), fried snacks (116 (55.2%)), fruits (96 (45.7%)), and juices (20 (9.5%)). Large proportion of the patients (112 (53.6%)) consumed more food calories than recommended. Use of fried snacks was significant in patients who consumed alcohol ( P = 0.03) and patients who had diabetes mellitus were more likely to use saturated fats ( P = 0.01). Discussion: Majority of the patients consumed milk and milk products. Fruits and juices were consumed by a small proportion of patients. Our results provide opportunities for stroke prevention by diet modification.